A polyurethane composite material for solar photovoltaic power generation frame and bracket
By using end epoxy polybutadiene of nitrogen-phosphorus flame retardant elements and covalent graft-modified polyethylene fibers in polyurethane composites, polyurethane composites are solved to resist UV in solar photovoltaic power generation frames and brackets. The problem of poor properties and flame retardancy achieves the efficient flame retardant and UV resistance of the material, extends the service life and reduces environmental risks.
Patent Information
- Application Number
- CN202411389453.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Polyurethane composites have poor UV resistance and flame retardancy in solar photovoltaic frames and bracket applications, resulting in short service life and potential environmental hazards.
The end epoxy polybutadiene containing nitrogen-phosphorus flame retardant elements in the structure is used as a composite flame retardant, and the polyethylene fibers are chemically connected to fullerene by covalent grafting to prepare excellent Polyurethane composite materials that resist UV and flame retardant properties.
It significantly improves the flame retardant and UV resistance of polyurethane composites, extends its service life, and reduces the risk of environmental damage.
Smart Images

Figure CN118895045B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a polyurethane composite material used for a solar photovoltaic power generation frame and a bracket. Background Art
[0002] As environmental problems become increasingly serious, people's demand for clean energy has increased dramatically. As an important renewable resource, solar energy and its photovoltaic power generation technology have received widespread attention and application. Among them, solar photovoltaic power generation frames and brackets are important components of photovoltaic power generation systems. They are structural materials mainly used to support and fix photovoltaic components. At present, the materials used for solar photovoltaic frames and brackets are mainly aluminum alloy materials. However, solar photovoltaic frames and brackets made of aluminum alloy materials have problems such as poor insulation, high cost, and poor impact resistance. In order to solve this problem, the industry has gradually considered the use of lightweight insulating polyurethane composite materials as an alternative or supplement.
[0003] Polyurethane composite materials are made of raw materials such as polyols and isocyanates through condensation reactions. Since they can be cured at room temperature, formed under normal pressure, and have flexible process performance, they are often used in pultruded products. With the rapid development of the photovoltaic industry in recent years and the new application environment requirements for photovoltaic materials, the performance requirements for polyurethane composite materials are becoming increasingly higher. Since solar photovoltaic equipment is exposed to sunlight for a long time during use, and the ultraviolet rays in sunlight have a catalytic degradation effect on polyurethane, if the polyurethane composite material has poor UV resistance, it is prone to aging and cracking after long-term use of solar photovoltaic frames and brackets, which leads to a relatively short service life of solar photovoltaic frames and brackets. In addition, polyurethane materials have poor flame retardancy and are easily decomposed into flammable small molecules under high temperature conditions. When burned, they release a large amount of heat and toxic gases, causing damage to the surrounding environment and shortening the service life, thereby greatly limiting their application in the photovoltaic field.
[0004] In the prior art, the improvement of the performance of polyurethane composite materials is mostly achieved by adding various functional additives and fillers to give polyurethane composite materials a variety of special properties. For example, the invention patent with the announcement number CN116003993B discloses an anti-ultraviolet aging polyurethane material and its preparation method and solar cell frame. The invention adds a modified hollow glass capillary in the matrix, and the sodium persulfate and titanate-cinnamate composition in the modified hollow glass capillary can absorb and consume ultraviolet rays, thereby improving the anti-ultraviolet performance of the material. Based on this, it is of great significance for the present invention to develop a polyurethane composite material with excellent anti-ultraviolet performance and flame retardant performance. Summary of the invention
[0005] The purpose of the present invention is to provide a polyurethane composite material for solar photovoltaic power generation frames and brackets, which solves the following technical problems:
[0006] (1) Solved the problem of poor UV resistance of polyurethane composite materials;
[0007] (2) The problem of poor flame retardancy of polyurethane composite materials was solved.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A polyurethane composite material for a solar photovoltaic power generation frame and bracket comprises the following raw materials in parts by weight: 30 to 40 parts of a compound flame retardant, 10 to 20 parts of an isocyanate monomer, 0.5 to 1.5 parts of a catalyst, 3 to 5 parts of a small molecule chain extender, 6 to 8 parts of a functional additive, 5 to 15 parts of talc, 2 to 3 parts of dioctyl phthalate, 1 to 3 parts of zinc stearate, and 1 to 2 parts of an antioxidant 168.
[0010] Furthermore, the preparation method of the composite flame retardant comprises the following steps:
[0011] D1: Add terminal epoxy polybutadiene and toluene into a nitrogen-protected reactor, stir evenly, add bis(dimethylsilyl)amine, turn on the heating until the temperature in the reactor reaches 50-70°C, keep stirring for 6-9 hours, and remove the solvent by rotary evaporation to obtain modified terminal epoxy polybutadiene;
[0012] D2: Under nitrogen protection, the modified terminal epoxy polybutadiene was placed in a dimethyl sulfoxide solution, ultrasonically dispersed for 20 to 30 minutes, diethyl vinyl phosphonate and platinum catalyst were added, and the system temperature was raised to 60 to 80°C under stirring conditions, kept warm for 3 to 5 hours, cooled and discharged to obtain a composite flame retardant.
[0013] Furthermore, in step D1, the epoxy value of the epoxy-terminated polybutadiene is 0.4 to 0.6 mmol / g.
[0014] Furthermore, in step D2, the platinum catalyst is a Custer catalyst, and the amount of the Custer catalyst added is 0.1 to 0.2% of the total mass of the modified terminal epoxy polybutadiene and diethyl vinyl phosphonate.
[0015] Furthermore, the preparation method of the functional additive comprises the following steps:
[0016] DD1: adding polyethylene fiber to acetone, soaking for 10 to 20 minutes to remove surface impurities, then washing with deionized water, drying to obtain cleaned polyethylene fiber, and then using plasma equipment to treat the cleaned polyethylene fiber, setting the equipment power to 50 to 100 W and the pressure to 25 to 35 Pa, first using oxygen to treat for 80 to 100 seconds, and then using nitrogen to treat for 110 to 130 seconds to obtain pretreated polyethylene fiber;
[0017] DD2: Add the pretreated polyethylene fiber and 2-aminoethanethiol to the toluene solution, ultrasonicate until a uniform suspension is formed, pass nitrogen, exhaust the air, add the accelerator and condensation agent to the suspension, raise the temperature to 55-65°C, stir for 4-6 hours, remove the nitrogen, filter, collect the product, and vacuum dry to obtain the modified polyethylene fiber;
[0018] DD3: Add modified polyethylene fiber, fullerene and N,N-dimethylformamide into the reactor, ultrasonically treat for 30 to 50 minutes, introduce nitrogen to deoxygenate, continue to add initiator, and after addition, increase the system temperature to 135 to 145°C, stir for 4 to 10 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain a functional additive.
[0019] Furthermore, in step DD1, the polyethylene fibers have an average diameter of 3 μm and an average length of 5 mm.
[0020] Furthermore, in step DD2, the accelerator is any one of 1-hydroxybenzotriazole and 4-dimethylaminopyridine; and the condensing agent is any one of N,N'-diisopropylcarbodiimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide.
[0021] Furthermore, in step DD3, the initiator is any one of dipropylbenzene peroxide or benzoyl peroxide.
[0022] Furthermore, the isocyanate monomer is any one of isophorone diisocyanate, hexamethylene diisocyanate or toluene-2,4-diisocyanate; the catalyst is any one of stannous octoate, dibutyltin dilaurate or dimorpholinyl diethyl ether; and the small molecule chain extender is any one of 1,4-butanediol, 1,3-propylene glycol or ethylene glycol.
[0023] Furthermore, the preparation method of the polyurethane composite material comprises the following steps:
[0024] Ⅰ: Add the compound flame retardant and isocyanate monomer into a reaction kettle, stir and mix, pass nitrogen, exhaust the air, add the catalyst, stir for 1 to 3 hours at a temperature of 70 to 90°C, then add the small molecule chain extender, continue stirring for 1 to 2 hours to obtain a polyurethane prepolymer;
[0025] II: adding functional additives, talcum powder, dioctyl phthalate, zinc stearate and antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0026] III: placing the mixed material in a pultrusion molding machine, setting the mold temperature of the pultrusion molding machine to 80-150° C., the pulling speed to 1-3 m / min, and finally demolding to obtain a polyurethane composite material.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention adopts epoxy-terminated polybutadiene having nitrogen-phosphorus flame retardant elements in its structure as a composite flame retardant. Since its structure contains active hydroxyl groups, it can undergo condensation reaction with isocyanate monomers, etc., thereby introducing nitrogen-phosphorus flame retardant elements into the main chain of polyurethane. The presence of nitrogen-phosphorus synergistic flame retardant can make the prepared polyurethane composite material have good flame retardant properties. According to tests, the limiting oxygen index of the prepared polyurethane composite material can reach up to 33.8%, which can effectively prevent the spread of fire, reduce fire losses and extend its service life when a fire occurs. In addition, the presence of epoxy-terminated polybutadiene can improve the toughness of the polyurethane composite material, avoid cracks, deformation or breakage of the polyurethane composite material when it is impacted by wind or other external factors, thereby extending its service life and reducing maintenance costs.
[0029] (2) The present invention chemically connects polyethylene fiber and fullerene by covalent grafting to obtain a functional additive. After organic modification, the polyethylene fiber can effectively improve its compatibility with the matrix, promote the uniform dispersion of the functional additive in the matrix, and can stably exist in the polyurethane composite material, thereby maximizing the advantages of the polyethylene fiber and giving the polyurethane composite material excellent mechanical properties to cope with complex application environments and ensure that the structural integrity and functional effectiveness can be maintained during long-term use. In addition, the fullerene in the functional additive has excellent UV resistance. Introducing it into the polyurethane composite material can enhance the UV resistance of the polyurethane composite material, avoid aging and cracking of solar photovoltaic frames and brackets after long-term use, and further extend the service life of the polyurethane composite material.
[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0032] Figure 1 This is an infrared spectrum test chart of the modified terminal epoxy polybutadiene and the compound flame retardant prepared in Example 1 of the present invention.
[0033] Figure 2 This is an infrared spectrum test chart of the functional additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The preparation methods of the compounded flame retardants and functional additives in the following examples and comparative examples of the present invention are as follows:
[0036] 1. Preparation of compound flame retardant
[0037] D1: 5 g of epoxy-terminated polybutadiene with an epoxy value of 0.5 mmol / g and toluene were added to a nitrogen-protected reactor, stirred evenly, and then 1.2 g of bis(dimethylsilyl)amine was added. The heating was turned on until the temperature in the reactor reached 60° C. The mixture was stirred for 7 h at the temperature, and the solvent was removed by rotary evaporation to obtain a modified epoxy-terminated polybutadiene.
[0038] The above-mentioned epoxy-terminated polybutadiene and bis(dimethylsilyl)amine The reaction equation is:
[0039]
[0040] D2: Under nitrogen protection, 5 g of modified terminal epoxy polybutadiene was placed in a dimethyl sulfoxide solution and ultrasonically dispersed for 25 min. 1.4 g of diethyl vinylphosphonate and 0.01 g of platinum (0)-1,3-diethenyl-1,1,3,3-tetramethyldisiloxane were added. The system temperature was raised to 70 ° C under stirring conditions, kept warm for 4 h, cooled and discharged to obtain a composite flame retardant.
[0041] The modified epoxy-terminated polybutadiene and compound flame retardant were analyzed by infrared spectroscopy using Nicolet 800 Fourier transform infrared spectrometer. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of modified epoxy-terminated polybutadiene, The characteristic absorption peak of hydroxyl group OH appears at The characteristic absorption peak of Si-H appears at The characteristic absorption peak of CN appears at The characteristic absorption peak of C-Si appears at The characteristic absorption peak of Si-N appears at The characteristic absorption peak of ether bond COC appears at ; in the infrared spectrum of the compound flame retardant, The characteristic absorption peak of hydroxyl group OH appears at The characteristic absorption peak of CN appears at The characteristic absorption peak of C-Si appears at the The characteristic absorption peak of Si-N appears at The characteristic absorption peak of ether bond COC appears at The absorption peak of P=O appears at The absorption peak of PO appears at the center, and the characteristic absorption peak of Si-H disappears.
[0042] It can be inferred that the principle of the above scheme is: the epoxy group in the terminal epoxy polybutadiene structure can undergo a ring-opening reaction with the imino group in the bis(dimethylsilyl)amine structure, and the bis(dimethylsilyl)amine is introduced into the structure of the terminal epoxy polybutadiene. At the same time, the ring-opening reaction produces active hydroxyl groups to obtain modified terminal epoxy polybutadiene. Then, under the catalytic action of platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, the Si-H in the modified terminal epoxy polybutadiene structure can undergo a silylation reaction with the alkenyl group in the diethyl vinylphosphonate structure to obtain a composite flame retardant.
[0043] 2. Preparation of functional additives
[0044] DD1: 6 g of polyethylene fibers with an average diameter of 3 μm and an average length of 5 mm were added to acetone and soaked for 15 min to remove surface impurities, then washed with deionized water and dried to obtain cleaned polyethylene fibers, and then treated with a plasma device with a power of 80 W and a pressure of 30 Pa. The fibers were first treated with oxygen for 90 s and then with nitrogen for 120 s to obtain pretreated polyethylene fibers.
[0045] DD2: Add 6 g of pretreated polyethylene fiber and 1.5 g of 2-aminoethanethiol to the toluene solution, sonicate until a uniform suspension is formed, pass nitrogen, exhaust the air, add 0.05 g of 1-hydroxybenzotriazole and 0.1 g of N,N'-diisopropylcarbodiimide to the suspension, raise the temperature to 60°C, stir for 5 h, remove nitrogen, filter, collect the product, and vacuum dry to obtain modified polyethylene fiber;
[0046] DD3: Add 6 g of modified polyethylene fiber and 2.2 g of fullerene (C 60 ) and N, N-dimethylformamide, ultrasonically treat for 40 minutes, introduce nitrogen for deoxygenation, continue to add 0.1g of dipropylbenzene peroxide, after the addition, raise the system temperature to 140°C, stir for 6 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain a functional additive.
[0047] The functional additives were analyzed by infrared spectroscopy using Nicolet 800 Fourier transform infrared spectrometer, such as Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of functional additives, The characteristic absorption peak of NH in amide appears at The characteristic absorption peak of C=O in amide appears at The characteristic absorption peak of CSC appears at The characteristic absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at .
[0048] It can be inferred that the principle of the above scheme is: since polyethylene fiber has fewer active groups and is more inert, plasma is used to treat polyethylene fiber to produce active functional groups such as carboxyl groups on the surface of polyethylene fiber, and the carboxyl groups on its surface are used as active sites. Under the action of 1-hydroxybenzotriazole and N,N'-diisopropylcarbodiimide, the carboxyl groups and the amino groups in the structure of 2-aminoethanethiol can react to introduce 2-aminoethanethiol to the surface of polyethylene fiber to obtain modified polyethylene fiber, and then under the action of dipropylbenzene peroxide, the thiol groups on the surface of the modified polyethylene fiber react with fullerene (C 60 ) reacts with the olefinic group in the structure to obtain functional additives. Example 1
[0049] Preparation of polyurethane composites
[0050] Ⅰ: 30g of compound flame retardant and 10g of hexamethylene diisocyanate were put into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 0.5g of dibutyltin dilaurate was added, and stirred at 70°C for 1h, and then 3g of 1,4-butanediol was added, and the stirring was continued for 1h to obtain a polyurethane prepolymer;
[0051] II: adding 6 g of functional additives, 5 g of talc, 2 g of dioctyl phthalate, 1 g of zinc stearate and 1 g of antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0052] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 80° C., the pulling speed to 1 m / min, and finally demolding to obtain a polyurethane composite material. Example 2
[0053] Preparation of polyurethane composites
[0054] Ⅰ: 35g of the compound flame retardant and 15g of hexamethylene diisocyanate were added into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 1g of dibutyltin dilaurate was added, and the mixture was stirred at 80°C for 2h, and then 4g of 1,4-butanediol was added, and the mixture was stirred for 1.5h to obtain a polyurethane prepolymer;
[0055] II: adding 7 g of functional additives, 10 g of talc, 2.5 g of dioctyl phthalate, 2 g of zinc stearate and 1.5 g of antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0056] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 120° C., the pulling speed to 2 m / min, and finally demolding to obtain a polyurethane composite material. Example 3
[0057] Preparation of polyurethane composites
[0058] Ⅰ: 40g of the compound flame retardant and 20g of hexamethylene diisocyanate were put into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 1.5g of dibutyltin dilaurate was added, and stirred at 90°C for 3h, and then 5g of 1,4-butanediol was added, and the stirring was continued for 2h to obtain a polyurethane prepolymer;
[0059] II: adding 8 g of functional additives, 15 g of talc, 3 g of dioctyl phthalate, 3 g of zinc stearate and 2 g of antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0060] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 150° C., the pulling speed to 3 m / min, and finally demolding to obtain a polyurethane composite material.
[0061] Comparative Example 1
[0062] Preparation of polyurethane composites
[0063] Ⅰ: 35g of the compound flame retardant and 15g of hexamethylene diisocyanate were added into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 1g of dibutyltin dilaurate was added, and the mixture was stirred at 80°C for 2h, and then 4g of 1,4-butanediol was added, and the mixture was stirred for 1.5h to obtain a polyurethane prepolymer;
[0064] II: adding 10 g of talc, 2.5 g of dioctyl phthalate, 2 g of zinc stearate and 1.5 g of antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0065] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 120° C., the pulling speed to 2 m / min, and finally demolding to obtain a polyurethane composite material.
[0066] Comparative Example 2
[0067] Preparation of polyurethane composites
[0068] Ⅰ: 35g of polytetramethylene diisocyanate and 15g of hexamethylene diisocyanate were added into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 1g of dibutyltin dilaurate was added, and the mixture was stirred at 80°C for 2h, and then 4g of 1,4-butanediol was added, and the mixture was stirred for 1.5h to obtain a polyurethane prepolymer;
[0069] II: adding 7 g of functional additives, 10 g of talc, 2.5 g of dioctyl phthalate, 2 g of zinc stearate and 1.5 g of antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0070] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 120° C., the pulling speed to 2 m / min, and finally demolding to obtain a polyurethane composite material.
[0071] Comparative Example 3
[0072] Preparation of polyurethane composites
[0073] Ⅰ: 35g of the compound flame retardant and 15g of hexamethylene diisocyanate were added into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 1g of dibutyltin dilaurate was added, and the mixture was stirred at 80°C for 2h, and then 4g of 1,4-butanediol was added, and the mixture was stirred for 1.5h to obtain a polyurethane prepolymer;
[0074] Ⅱ: 4g polyethylene fiber, 3g fullerene (C 60 ), 10 g of talc, 2.5 g of dioctyl phthalate, 2 g of zinc stearate and 1.5 g of antioxidant 168 are added to the polyurethane prepolymer prepared in step I, and stirred evenly to obtain a mixed material;
[0075] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 120° C., the pulling speed to 2 m / min, and finally demolding to obtain a polyurethane composite material.
[0076] Comparative Example 4
[0077] Preparation of polyurethane composites
[0078] Ⅰ: 35g of polytetramethylene diisocyanate and 15g of hexamethylene diisocyanate were added into a reaction kettle, stirred and mixed, nitrogen was passed through, and after the air was exhausted, 1g of dibutyltin dilaurate was added, and the mixture was stirred at 80°C for 2h, and then 4g of 1,4-butanediol was added, and the mixture was stirred for 1.5h to obtain a polyurethane prepolymer;
[0079] II: adding 10 g of talc, 2.5 g of dioctyl phthalate, 2 g of zinc stearate and 1.5 g of antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material;
[0080] III: placing the mixed material in a pultrusion machine, setting the mold temperature of the pultrusion machine to 120° C., the pulling speed to 2 m / min, and finally demolding to obtain a polyurethane composite material.
[0081] Performance testing:
[0082] The polyurethane composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention were made into samples that met the test specifications. The samples were subjected to a combustion performance test according to GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test" to evaluate the flame retardant properties of the samples; the samples were subjected to a tensile strength and elongation at break test according to GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles"; the samples were placed under a wavelength of 313 nm and an irradiance of 0.72 m 2The samples were treated in a UV aging box for 36 hours, and then the tensile strength test was performed on the samples to determine the UV resistance of the samples; the impact strength test was performed on the samples according to GB / T 1843-2008 "Determination of the impact strength of plastic cantilever beams", and the specific test results are shown in the following table:
[0083] Table 1 - Performance Test
[0084]
[0085] From the test results in the above table, it can be seen that the samples prepared in Examples 1 to 3 all have excellent flame retardancy, toughness, UV resistance and mechanical properties; in the sample prepared in Comparative Example 1, no functional additives were added, so the sample was at a relatively poor level in terms of UV resistance and mechanical properties, but a compound flame retardant was added therein, so the flame retardancy and toughness of the sample were good; in the sample prepared in Comparative Example 2, functional additives were added, and compared with the examples, the UV resistance and mechanical properties of the sample were excellent, but since no compound flame retardant was added therein, the toughness and flame retardancy of the sample were at a relatively poor level; in the sample prepared in Comparative Example 3, polyethylene fiber was directly added without modification, although a compound flame retardant and fullerene (C 60 ), but the sample performed generally in terms of UV resistance and mechanical properties, which was caused by the agglomeration of the unmodified polyethylene fibers in the matrix material; the sample prepared in Comparative Example 4 had neither the addition of compound flame retardants nor functional additives, so the sample was at a poor level in all performances.
[0086] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A polyurethane composite material for solar photovoltaic power generation frames and brackets, characterized in that: The invention comprises the following raw materials in parts by weight: 30 to 40 parts of compound flame retardant, 10 to 20 parts of isocyanate monomer, 0.5 to 1.5 parts of catalyst, 3 to 5 parts of small molecule chain extender, 6 to 8 parts of functional additive, 5 to 15 parts of talc, 2 to 3 parts of dioctyl phthalate, 1 to 3 parts of zinc stearate, and 1 to 2 parts of antioxidant 168; The preparation method of the composite flame retardant comprises the following steps: D1: Add terminal epoxy polybutadiene and toluene into a nitrogen-protected reactor, stir evenly, add bis(dimethylsilyl)amine, turn on the heating until the temperature in the reactor reaches 50-70°C, keep stirring for 6-9 hours, and remove the solvent by rotary evaporation to obtain modified terminal epoxy polybutadiene; D2: Under nitrogen protection, the modified terminal epoxy polybutadiene is placed in a dimethyl sulfoxide solution, ultrasonically dispersed for 20 to 30 minutes, diethyl vinylphosphonate and a platinum catalyst are added, and the system temperature is raised to 60 to 80°C under stirring conditions, kept warm for 3 to 5 hours, cooled and discharged to obtain a composite flame retardant; The preparation method of the functional additive comprises the following steps: DD1: adding polyethylene fiber to acetone, soaking for 10 to 20 minutes to remove surface impurities, then washing with deionized water, drying to obtain cleaned polyethylene fiber, and then using plasma equipment to treat the cleaned polyethylene fiber, setting the equipment power to 50 to 100 W and the pressure to 25 to 35 Pa, first using oxygen to treat for 80 to 100 seconds, and then using nitrogen to treat for 110 to 130 seconds to obtain pretreated polyethylene fiber; DD2: Add the pretreated polyethylene fiber and 2-aminoethanethiol to the toluene solution, ultrasonicate until a uniform suspension is formed, pass nitrogen, exhaust the air, add the accelerator and condensation agent to the suspension, raise the temperature to 55-65°C, stir for 4-6 hours, remove the nitrogen, filter, collect the product, and vacuum dry to obtain the modified polyethylene fiber; DD3: Add modified polyethylene fiber, fullerene and N,N-dimethylformamide into the reactor, ultrasonically treat for 30 to 50 minutes, introduce nitrogen to deoxygenate, continue to add initiator, and after addition, increase the system temperature to 135 to 145°C, stir for 4 to 10 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain a functional additive.
2. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: In step D1, the epoxy value of the epoxy-terminated polybutadiene is 0.4-0.6 mmol / g.
3. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: In step D2, the platinum catalyst is a Custer catalyst, and the amount of the Custer catalyst added is 0.1 to 0.2% of the total mass of the modified terminal epoxy polybutadiene and diethyl vinyl phosphonate.
4. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: In step DD1, the polyethylene fibers have an average diameter of 3 μm and an average length of 5 mm.
5. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: In step DD2, the accelerator is any one of 1-hydroxybenzotriazole and 4-dimethylaminopyridine; the condensing agent is any one of N,N'-diisopropylcarbodiimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide.
6. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: In step DD3, the initiator is any one of dipropylbenzene peroxide or benzoyl peroxide.
7. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: The isocyanate monomer is any one of isophorone diisocyanate, hexamethylene diisocyanate or toluene-2,4-diisocyanate; the catalyst is any one of stannous octoate, dibutyltin dilaurate or dimorpholinyl diethyl ether; and the small molecule chain extender is any one of 1,4-butanediol, 1,3-propylene glycol or ethylene glycol.
8. The polyurethane composite material for solar photovoltaic power generation frame and bracket according to claim 1, characterized in that: The preparation method of the polyurethane composite material comprises the following steps: Ⅰ: Add the compound flame retardant and isocyanate monomer into a reaction kettle, stir and mix, pass nitrogen, exhaust the air, add the catalyst, stir for 1 to 3 hours at a temperature of 70 to 90°C, then add the small molecule chain extender, continue stirring for 1 to 2 hours to obtain a polyurethane prepolymer; II: adding functional additives, talcum powder, dioctyl phthalate, zinc stearate and antioxidant 168 to the polyurethane prepolymer prepared in step I, stirring evenly to obtain a mixed material; III: placing the mixed material in a pultrusion molding machine, setting the mold temperature of the pultrusion molding machine to 80-150° C., the pulling speed to 1-3 m / min, and finally demolding to obtain a polyurethane composite material.
Citation Information
Patent Citations
An anti-UV aging polyurethane material, its preparation method, and a solar cell frame
CN116003993B
Preparation method of nanogold-fullerene nano composite material
CN101961785A
Preparation method of light-resistant and waterproof water-based flame retardant polyurethane coating and adhesive
CN104194607A
Cited By
Preparation method and application of reinforced polyurethane resin for photovoltaic frame
CN120795274A
Flame-retardant polyurethane resin system capable of realizing high-speed pultrusion
CN121801041A